Protein photodegradation in the visible range? Insights into protein photooxidation with respect to protein concentration - Elena Hipper; Florian Lehmann; Wolfgang Kaiser; Göran Hübner; Julia Buske; Michaela Blech; Dariush Hinderberger; Patrick Garidel (Elsevier, 2023)
Visible light (400-800 nm) can lead to photooxidation of protein formulations, which might impair protein integrity. However, the relevant mechanism of photooxidation upon visible light exposure is still unclear for therapeutic proteins, since proteinogenic structures do not absorb light in the visible range. Here, we show that exposure of monoclonal antibody formulations to visible light, lead to the formation of reactive oxygen species (ROS), which subsequently induce specific protein degradations. The formation of ROS and singlet oxygen upon visible light exposure is investigated using electron paramagnetic resonance (EPR) spectroscopy. We describe the initial formation of ROS, most likely after direct reaction of molecular oxygen with a triplet state photosensitizer, generated from intersystem crossing of the excited singlet state. Since these radicals affect the oxygen content in the headspace of the vial, we monitored photooxidation of these mAb formulations. With increasing protein concentrations, we found (i) a decreasing headspace oxygen content in the sample, (ii) a higher relative number of radicals in solution and (iii) a higher protein degradation. Thus, the protein concentration dependence indicates the presence of higher concentration of a currently unknown photosensitizer.